Perceptual load modulates the delta oscillation and the contribution of delta oscillation to reward positivity during feedback valence encoding - Qi, Congcong; Zhu, Jinming; Chen, Lele; Tong, Lingyao; Jia, Shiwei (Frontiers in Psychology, 2025)
RewP (reward positivity) and P300 are feedback-related ERP components, while delta and theta are oscillatory responses evoked during feedback processing. While the perceptual difficulty of feedback modulates ERP components, its impact on feedback-related oscillatory activities remains unexplored. In this study, the perceptual load of feedback stimuli was manipulated to investigate its influence on the valence effect of both ERP and oscillatory components. Further, the contribution of the oscillations’ valence effect (e.g., the difference wave between positive and negative feedback) to the valence effect of ERP components was analyzed, alongside the moderation of perceptual load on these contributions. The results indicated that, for both the RewP and P300, the amplitudes evoked by positive feedback were greater than those evoked by negative feedback. For theta oscillation, however, the activity evoked by negative feedback was stronger than that evoked by positive feedback. These valence effects were unaffected by perceptual load. However, for delta oscillation, its valence effect was modulated by perceptual load, only under low-load conditions did positive feedback elicit greater delta activity than negative feedback. The correlation analysis for the difference wave between positive and negative feedback showed that the RewP was significantly correlated with the P300, while delta and theta activities were not significantly correlated. The regression analysis of the difference wave revealed that delta significantly predicted the RewP under low-load conditions, while theta significantly predicted the P300 under high-load conditions. These results suggest that delta and theta oscillations reflect the processing of positive and negative feedback, respectively. Perceptual load modulates only positive feedback processing; the lower the load, the easier the processing. Perceptual load also modulates the contribution of delta oscillation to the RewP, but not to the P300.